Some of clinical characteristics of neonatal sepsis in Children's hospital at Kirkuk city, Iraq (Eurasian Medical Research Periodical, 2022)
Neonatal sepsis is a significant cause of mortality & long-term morbidity. The preterm infant has high-risk for sepsis & its sequelae . Low birth weight neonates were more susceptible to sepsis. This study aims to describe some of characteristics of neonatal sepsis in neonatology intensive care unit of pediatric hospital